Electron and positron scattering by atomic rubidium / Chin Jia Hou - Chin, Jia Hou (2011)
Electron and positron scattering from the Rubidium atom is studied using the coupled-channel optical method (CCOM). This method incorporates the continuum effect within the close coupling method (CC) by including an optical potential into the calculations. For electron-Rubidium scattering, a 5-state [Rb(5s, 5p, 4d, 6s, 6p)] and 8-state [Rb(5s, 5p, 4d, 6s, 6p, 5d, 7s, 7p)] CC and CCO calculations are carried out. For positron-Rubidium scattering, a 8-state [Rb(5s, 5p, 4d, 6s, 6p) + Ps(1s, 2s, 2p)], 11-state [Rb(5s, 5p, 4d, 6s, 6p) + Ps(1s, 2s, 2p, 3s, 3p, 3d) and Rb(5s, 5p, 4d, 6s, 6p, 5d, 7s, 7p) + Ps(1s, 2s, 2p)] and a 14-state [Rb(5s, 5p, 4d, 6s, 6p, 5d, 7s, 7p) + Ps(1s, 2s, 2p, 3s, 3p, 3d)] calculations are carried out. The elastic, excitation, differential and total cross sections are reported and compared to other theoretical data and experimental measurements.